THE PECULIARITIES OF THE DATA OF INSTRUMENTAL EXAMINATIONS OF WOMEN AFFECTED BY UTERINE FIBROIDS WITH CONCOMITANT HEPATOBILIARY DISEASES (World Science, 2021)
Nowadays, women’s reproductive health is a topical issue of obstetrics and gynecology, therefore, great importance is attributed to timely diagnosis and prevention of diseases that influence fertility. The topicality of the issue of uterine hyperplasia, in particular, uterine fibroids, is accounted for by the social significance of the disease. Its incidence rate is constantly growing and makes up from 30 to 50% in women older than 35 years and, according to the data of autopsy, - up to 80%. No doubt, the peculiarities of development and progression of hyperplasia are determined by the reserve potential of various systems and organs, including the hepatobiliary system.The aim of research is to analyze the results of instrumental examinations of the functional capacity of hepatocytes in women affected by uterine fibroids and functional disorders of the hepatobiliary system. Research materials and methods. To accomplish the set objective, we used the following contemporary instrumental examination methods: ultrasonography and rheovasohepatography as well as a clinical and paraclinical analysis of caserecords of 150 women aged between 35 and 45 and affected by uterine fibroids, who were treated at the gynecological department of the Regional Perinatal Centre.Research results. As the research result show, uterine fibroids and the related hormonal disorders often go together with functional and morphological lesion of hepatocytes. Patients affected by uterine fibroids have preconditions for the development of functional disorders of hepatocytes as they present significant disorders of hepatic hemodynamics, decreased blood supply of the liver, as a result of pre- and postcapillary resistance.Conclusions. There is a close connection between uterine fibroids with concomitant hepatobiliary disorders and the severity of hormonal disorders, and the significant lesion of hepatocytes may be irreversible. Thisrequires pathogenetic correction by introducing drugs with hepatoprotective and antioxidant effects.